Switching-median denoising with boundary discriminative noise detection for highly corrupted images - Ng, Pei Eng. (2008)
The main objective of this dissertation is to further research and propose a new noise detection algorithm, called boundary discriminative noise detection (BDND), that shows distinct improvement over the previous works.